Guarding the neighbourhoods: The new landscape of control in Malaysia / Peter Aning Tedong - Peter, Aning Tedong (2014)

(untitled)
enclosures emerged as a topic of scholarly interest in the 1990s, international studies have proliferated. While some may argue that securitised enclosures are a global phenomenon, case studies of particular regions reveal enclosures take different forms in different nations as housing producers respond to local values, beliefs, and practices. In Malaysia, this study identified two types of enclosures being produced in sub/urban residential areas. In new development projects private developers are building gated communities surrounded by walls containing attractive shared amenities. In older areas, residents’ associations organise to create guarded neighbourhoods by erecting physical barriers across public roads, hiring security guards and impose makeshift boundaries to limit outsiders’ access. Therefore, through a political-economy approach based on neoliberalism, this study aimed to investigate the proliferation of guarded neighbourhoods in the Selangor state, Malaysia. In particular, this study examined the factors producing them, the role of governance and multiple key actors and the social spatial implications of this kind of community. This study developed these insights from a qualitative research that included in-depth interviews with multiple key actors in the government and communities, reviews of documentation and statistics, and direct-observations assessing guarded neighbourhoods in Selangor state, Malaysia. In-depth interviews revealed that safety and security – that is, fear of crime/other has motivated sub/urban residents to live in guarded neighbourhood. As the middle class has grown, the desire for private and exclusive living and to enhance property values also drives the creation of guarded neighbourhoods. In the context role of the state, research findings revealed that the Malaysian government, corporations, and citizen group’s work within a complex governance system to (re)produce guarded neighbourhoods and creating conditions that support enclosure and securitisation of space. A neoliberal government practices provide a regulatory context within which residents organise associations, levy fees, erect barricades, and hire guards to control formerly public streets and spaces. This study also revealed that guarded neighbourhood simultaneously reflect social exclusion—of non-residents and foreigners—and cohesive social action of the politically powerful to produce neighbourhood identity and community coherence. Citizen action to create guarded neighbourhoods reveals emerging class boundaries and reinforces social segregation and urban fragmentation in urban Malaysia. In sum, this study showed that neoliberal market principles fuse with ethnic politics, cultural predilections, and economic imperatives to generate a socially and spatially fragmented urban landscape where security concerns dominate and where citizens culturally, physically, and symbolically segregate themselves from others. As the power of urban practitioners working with the Malaysian government proved limited, this study also recommended some improvements on the existing roles and rules in governing and reproducing guarded neighbourhoods in Malaysia.